X2 - 16X + 15 = 0 (X - 1)(X - 15) = 0 So X -1 = 0 or X - 15 = 0 ie X = 1 or X = 15
(5, 1)
(2, 1)
x = 0
y=x+1 there for answer is 2
9-5n+1 = 15 -5n = 15-9-1 -5n = 5 Divide both sides of the equation by -5 to find the value of n: n = -5
1 - 7n = 15 - 5n Add 5n to each side: 1 - 7n + 5n = 15 -5n + 5n ie 1 - 2n = 15; subtract 1 from each side: -2n = 14 divide both sides by -2: n = -7
5n + 1 = 10 + 2n5n - 2n + 1 - 1 = 10 - 1 + 2n - 2n3n = 93n/3 = 9/3n = 3
n=1 2/3
5n + 3 = 14 - 6n <=> 5n +6n = 14 - 3 <=> 11n = 11 => n = 11/11 = 1
1
4 over 5n
(2n+3)(n+1)=2n2+5n+3.
-6n + 2 - 5n = -9Combine like terms:-11n + 2 = -9Subtract 2 from each side:-11n = -11Divide both sides by -1:n = 1
Tenth term of 5n + 1 = 5*10 + 1 = 51
4 = -5n + 6n2 if you want to solve for n: 6n2 - 5n - 4 = 0 (3n - 4)(2n + 1) = 0 3n - 4 = 0, n = 4/3 2n + 1 = 0, n = -1/2 n = {-1/2, 4/3}
-14